Targeted Balance Training in Parkinsonism with Type 2 Diabetes and Hypertension: A Case Study - Alagappan, Thiyagarajane; Thangamani Ramaligam, Alagappan; S., Jeyakumar; S., Aravind (INTI International University, 2025)
Parkinsonism is a progressive neurological disorder where postural instability and impaired balance significantly elevate the risk of falls, especially in elderly individuals with comorbidities. The presence of Type 2 Diabetes Mellitus and hypertension further exacerbates fall risk by impairing sensory and cardiovascular responses. Early, structured physiotherapy interventions may mitigate fall risk and improve functional mobility. A single-subject case study was conducted involving a 75-year-old male diagnosed with idiopathic Parkinsonism (Hoehn and Yahr Stage 2), with controlled diabetes and hypertension. A 6-week physiotherapy program focuses on balance training, lower limb strengthening, and cognitive-motor integration. Sessions were conducted five times per week, lasting 45 minutes each. Outcomes were measured using the Berg Balance Scale (BBS) and Timed Up and Go (TUG) test at baseline and post-intervention. The patient showed significant improvement in both outcome measures. BBS scores increased from 35/56 to 48/56, indicating enhanced static and dynamic balance. TUG time decreased from 22.4 to 13.8 seconds, reflecting improved functional mobility and reduced fall risk. The intervention was well tolerated, with no adverse events reported. This case highlights the efficacy of a structured physiotherapy program tailored to the needs of an elderly Parkinsonism patient with multiple comorbidities. The improvements in balance and mobility underscore the importance of early intervention and individualized care. Integration of comorbidity-specific precautions further ensured safety and participation, promoting functional independence and fall prevention.